2015
DOI: 10.1111/conl.12209
|View full text |Cite
|
Sign up to set email alerts
|

Saving Tropical Forests by Knowing What We Consume

Abstract: Oil palm agriculture threatens tropical forests and biodiversity. Previous studies focused on finding ways to reduce the impacts of oil palm on biodiversity and the environment. However, the actual uptake of sustainable practices depends in part on economic demand. We undertook the first investigation on consumer attitudes and willingness-to-pay (WTP) for deforestation-free sustainable palm oil. In a sample of 251 consumers in Singapore, we found little consumer bias against palm oil per se. However, consumers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 28 publications
0
20
1
Order By: Relevance
“…The low cost of palm oil makes it one of the most challenging terrestrial crop oils to replace, this is even with an up to 10% estimated price uplift on consumer willingness to pay for a guaranteed deforestation-free product [86]. Processing changes that had the most substantial change to cost were the removal of extraction steps on downstream processing through extracellular lipid production, and the valorisation of a co-product priced >$1/kg reduced the minimum selling price of the lipid to $0 /kg.…”
Section: Implications Of This Study On Palm Oil Replacementmentioning
confidence: 99%
“…The low cost of palm oil makes it one of the most challenging terrestrial crop oils to replace, this is even with an up to 10% estimated price uplift on consumer willingness to pay for a guaranteed deforestation-free product [86]. Processing changes that had the most substantial change to cost were the removal of extraction steps on downstream processing through extracellular lipid production, and the valorisation of a co-product priced >$1/kg reduced the minimum selling price of the lipid to $0 /kg.…”
Section: Implications Of This Study On Palm Oil Replacementmentioning
confidence: 99%
“…In contrast to other conservation behaviours such as recycling or saving electricity, many consumers may not know that they can benefit the environment by reducing the amount of palm oil they consume. For example, most consumers surveyed by Giam et al (2016) did not seem to identify palm oil as a product that may cause deforestation (cf., Ostfeld et al 2019). However, when consumers are given information on the environmental consequences of palm oil, their knowledge about the issue appears to increase along with their support for mandatory palm oil labelling (Pearson et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to an online survey on community attitudes towards flying foxes in Australia (Kung et al 2015 ), male respondents were more likely to have a negative attitude towards flying foxes (Table 1A ). Kellert and Berry’s ( 1987 ) seminal study of American adults throughout the United States also found gender one of the most important demographic factors influencing attitudes towards wildlife and conservation, as have subsequent studies (e.g., Rauwald and Moore 2002 ; Dougherty et al 2003 ; Bjerke and Østdahl 2004 ; Miller and Jones 2006 ; Giam et al 2015 ; Koziarski et al 2016 ; Reid 2016 ). Our findings are consistent with this trend.…”
Section: Discussionmentioning
confidence: 85%